2004
DOI: 10.1258/0969141041732247
|View full text |Cite
|
Sign up to set email alerts
|

Screening for physical and psychological illness in the British Armed Forces: II: Barriers to screening – learning from the opinions of Service personnel

Abstract: Objective: To identify any potential barriers to the effectiveness of a military health screening programme based on the beliefs of British Service personnel. Methods:As part of a pilot evaluation of the suitability of a new health screening questionnaire for the British Armed Forces, 73 men and women from the three Services, of various ranks and age, underwent a semi-structured interview after completing a screening questionnaire. Participants were asked about the veracity of their answers and their views reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…It is likely that such deterrents are amplified in military culture where characteristics of strength, resilience, and self-sufficiency are selected for and prized. Our report that the most significant barrier to seeking mental health care is the anticipated stigma of consulting and lack of trust/confidence in mental health services mirrors what is reported for the US military [2,25], the Canadian military [1,26], and previously for the UK military [3,8]. Taken together these results suggest that despite recent efforts to de-stigmatise mental health problems, a substantial proportion of military personnel still anticipate stigma and believe that any help-seeking behaviour is likely to negatively impact their career and relationships with their seniors.…”
Section: Discussionsupporting
confidence: 70%
“…It is likely that such deterrents are amplified in military culture where characteristics of strength, resilience, and self-sufficiency are selected for and prized. Our report that the most significant barrier to seeking mental health care is the anticipated stigma of consulting and lack of trust/confidence in mental health services mirrors what is reported for the US military [2,25], the Canadian military [1,26], and previously for the UK military [3,8]. Taken together these results suggest that despite recent efforts to de-stigmatise mental health problems, a substantial proportion of military personnel still anticipate stigma and believe that any help-seeking behaviour is likely to negatively impact their career and relationships with their seniors.…”
Section: Discussionsupporting
confidence: 70%
“…Research supports these inferences about cultural beliefs towards mental health in military populations. It was observed in US military personnel that having a psychological problem is associated with much more stigma than suffering from a physical health problem;33 UK military research has suggested that it is viewed as more legitimate to suffer from a physical illness than a mental health illness,34 which is again supported by research that observed UK service personnel are much less likely to attend a first appointment for a psychological referral than a medical one 35. This apparent reluctance to attend appointments for psychological symptoms could be hypothesised as another factor for why, despite high rates of mental health problems and the availability of services, uptake of treatment is low within military populations.…”
Section: Stigma and Military Culturementioning
confidence: 97%
“…(11) Do you believe that you have fundamental rights that cannot be taken from you? (14) Do you believe that abortion is right or wrong? (17) † To what extent do you believe that organised religion is one of the main sources of human strife?…”
Section: Appendix: Cbq Questions (Question Order In Parentheses)mentioning
confidence: 99%
“…Stigma associated with mental illness is well recognised as an important factor influencing access to mental healthcare by the general population [13] . Indeed, a study of military personnel revealed that many had not honestly answered health screening questions for reasons of lack of trust in medical confidentiality, stigmatisation and fears that the process would jeopardise career prospects [14] . In particular older subjects, and especially women, are more likely to respond in a socially desirable manner [15,16] .…”
Section: Introductionmentioning
confidence: 99%